A new Costa Rican species of Leptanilloides (Hymenoptera: Formicidae: doryline section: Leptanilloidinae) - Longino, John T. (Zootaxa, 2003)
Leptanilloides mckennae sp. nov. is described from Costa Rica. This is the eighth species in the poorly-known subfamily Leptanilloidinae, part of the doryline section (army ants and relatives). The other seven species in the subfamily are from widely scattered localities in South America. The new species blurs previously established distinctions between Leptanilloides and Asphinctanilloides.